The Impact of Active and Passive Smoking upon Health and Neurocognitive Function - Thomas Heffernan (Frontiers Research Topics, 2016)
Tobacco smoking is a major risk factor for a number of chronic diseases, including a variety of cancers, lung disease and damage to the cardiovascular system. The World Health Organization recently calculated that there were 6 million smoking-attributable deaths per year and that this number is due to rise to about eight million per year by the end of 2030. Recent work has demonstrated that habitual smoking in adults is not only associated with a range of health problems, but may also contribute to a number of neurocognitive deficits, including deficits in memory and attention. One area of growing concern is the health and neurocognitive consequences of exposure to second-hand smoke or "passive smoking" (where a non-smoker inhales another person's smoke, mainly in the form of side-stream smoke). In terms of tackling smoking-related problems, there has been a rise in the amount and range of smoking cessation and interventions techniques, including the emergence of e-cigarettes as one of the most popular forms of nicotine replacement therapies. The present book comprises a collection of manuscripts discussing (1) the impact of active and passive smoking upon health and neurocognitive function, (2) smoking cessation techniques and interventions used to tackle smoking-related problems, and (3) a critical consideration of current issues surrounding the use of e-cigarettes as nicotine-replacement therapy. This collection of papers includes empirical, theoretical, and review papers. This Research Topic demonstrates the broad nature of research currently being undertaken in this field and should pave the way for future work.